Overexpression of Hyperpolarization‐Activated Cyclic Nucleotide‐Gated Channels into the Ventral Tegmental Area Increases the Rewarding Effects of Ethanol in UChB Drinking Rats. (24th January 2014) - Rivera‐Meza, Mario; Quintanilla, María Elena; Bustamante, Diego; Delgado, Ricardo; Buscaglia, Marianne; Herrera‐Marschitz, Mario
<x xml:space="preserve">Abstract</x> Background A number of studies have shown that ethanol (EtOH) activates dopamine neurocircuitries and is self‐administered into the ventral tegmental area (VTA) of the rat brain. In vitro and in silico studies have showed that hyperpolarization‐activated cyclic nucleotide‐gated (HCN) ionic channels on VTA dopamine neurons may constitute a molecular target of EtOH; however, there is no in vivo evidence supporting this assumption. Methods Wistar‐derived University of Chile Drinking (UChB) rats were microinjected into the VTA with a lentiviral vector coding for rat HCN‐2 ionic channel or a control vector. Four days after vector administration, daily voluntary EtOH intake was assessed for 30 days under a free‐access paradigm to 5% EtOH and water. After EtOH consumption studies, the effect of HCN‐2 overexpression was also assessed on EtOH‐induced conditioned place preference (CPP); EtOH‐induced locomotion, and EtOH‐induced dopamine release in the nucleus accumbens (NAcc). Results Rats microinjected with the HCN‐2 coding vector into the VTA showed (i) a 2‐fold increase in their voluntary EtOH intake compared to control animals, (ii) lentiviral‐HCN‐2‐treated animals also showed an increased CPP to EtOH ( 3‐fold), (iii) a significant higher locomotor activity ( 2‐fold), and (iv) increased dopamine release in NAcc upon systemic administration of EtOH ( 2‐fold). Conclusions Overexpression of HCN‐2 ionic channel in the VTA of rats results in an increase in voluntary EtOH intake, EtOH‐induced CPP, locomotor activity, and dopamine release in NAcc, suggesting that HCN levels in the VTA are relevant for the rewarding properties of EtOH.